Pengaruh Sales Growth, Kepemilikan Institusional dan Kepemilikan Asing Terhadap Tax Avoidance - Maria Renata; Ahalik (UNIVERSITAS KALBIS, 2022)
This research objective is to determine the influence of sales growth,Institusional ownership and foreign ownership on tax avoidance. This research uses quantitative methods. The population in this study is companies that have IPO in 2014-2016 with data processed in 2016-2018 listed on the Indonesia Stock Exchange. The sampel selection method uses saturated sampling totaling 28 copanies with 84 observations based on certain criteria. Data analysis method used in this reseach is descriptive analysis and multiple linear regression analysis using SPSS version 25 application. The results of this study are that sales growth has a significant effect on tax avoidance. while institusional ownelship does not significantly infuence tax avoidance. In addition, foreign ownerships has nosignficant effect on tax avoidance. In addition, foreign ownership has no significant effect ion tax avoidance.